Catholic Ethics and Capitalism in Latin America - González Manrique, Luis Esteban (1996)
This article argues that the ideas of Pope John Paul II appear to mark a long-awaited reconciliation between catholic ethics and capitalism. The two were hopelessly at odds at a time when “modern” as a concept in Latin America was understood as the elimination of all links with the Spanish monarchy. It is certainly true that “the troops of the independence movement marched under the standards of the Virgins of Luján, Guadalupe and Chiquinquirá”. However, a radical lay movement emerged toward the end of the 19th century. The council promoted reconciliation between liberal values and Catholic tradition. Demo-Christians thinking gathered force while radical socialism spurred on by liberation theology rose up to meet it. John Paul II seems to have shown us the light at the end of this particular tunnel.